Tactical procurement management and service delivery in local governments of Uganda: a case of Nebbi district local government - Cankwo, Paul; Obanda, Peter W.; Pule, Samuel (European Journal of Logistics Puchasing and Supply Chain Management, 2015)
The Public procurement in Uganda and the rest of the world is increasingly coming under pressure to go beyond the implementation of policies and procedures and to produce results in service delivery. However in Uganda despite the availability of institutional frame work and policies, there have been some challenges in the management of tactical procurement to yield the expected results. This study was conducted to examine the influence of tactical procurement process, competence of stake holders and strategic interventions in tactical procurement in Nebbi District Local Government. Structured questionnaires were developed and administered to asample size of 84 public procurement stakeholders in Nebbi District. Data was analyzed and interpreted using mean and the regression model. The study revealed that tactical procurement management greatly influences service delivery by (R2 value 61%, and Sig. = 0.000), which was largely attributed to the high levels at which competence of procurement management stakeholders influenced service delivery in Nebbi District (r2 = 68%, Sig. 0.046). It was noted that most of the stakeholders still have procurement knowledge gaps hence affecting service delivery management in the District. The findings further revealed that tactical procurement process and strategic interventions statistically have insignificant influence on service delivery in this study. Itwas concluded that tactical procurement management can positively influence service delivery in the District, and it was recommended that the District should put more resources in building capacities of stakeholders.
Keywords: Tactical Procurement Management; Tactical Procurement Process; ,Competence of Stakeholders; Strategic Intervention in Tactical Procurement; Service Delivery